Bioeffect of static magnetic field on photosynthetic bacteria: Evaluation of bioresources production and wastewater treatment efficiency. (9th March 2020) - Lu, Haifeng; Wang, Xiaodan; Hu, Shunfan; Han, Ting; He, Shichao; Zhang, Guangming; He, Mou; Lin, Xinyu
Abstract: Photosynthetic bacteria (PSB) technology is a promising method for biomass, protein, pigments, and other value‐added substances generation from wastewater. However, the above bioresources production efficiency is relatively low. In this work, a static magnetic field (SMF) was used to promote bioresources production. Results showed that SMF had positive effects on value‐added substances production. With 0.35 Tesla (T) SMF, the PSB biomass, protein, carotenoids, and bacteriochlorophyll concentration were promoted by 31.1%, 22.6%, 56.7%, and 73.1% compared with the control group, respectively. Biomass yield finally reached 0.58 g biomass/g COD removal, which was promoted by 37.1%. The doubling time was shortened by 37.9% in 0.35 T group, showing that SMF can promote cell growth. With 0.35 T SMF, the intracellular NADH dehydrogenase and ATP synthase activities concentration increased by 23.4% and 29.1%, respectively, thus increased the ATP content by 38.0%. Succinic dehydrogenase activity concentration greatly increased by 609.0% at 48 hr, which potentially accelerated the tricarboxylic acid cycle and COD degradation as well as enhanced biomass production. Practitioner points: SMF promoted PSB bioresource production during wastewater treatment processing. Biomass, protein, carotenoids, and Bchl concentration were promoted by 31.1%, 22.6%, 56.7%, and 73.1%, respectively. PSB yield of 0.35 T group was promoted by 37.1% compared with the control group. SDH concentration of 0.35 T was promoted by 609.0% compared with the control group. Increased NADH and ATP synthase activity concentration by SMF enhanced energy metabolism. Abstract : SMF takes effect on Photosynthetic bacteria Metabolism. 0.35 T SMF promote the intracellular NADH dehydrogenase, ATP synthase and succinic dehydrogenase activities concentration by 23.4%, 29.1% and 609%, respectively, leading to 38.0% ATP, 31.1% biomass, 22.6% protein, 56.7% carotenoids, 73.1% bacteriochlorophyll concentration and 37.1% cell yield promotion.